Factors affecting the use of long term and permanent contraceptive methods: a Facebook-focused cross-sectional study - Naser Al-Husban; Dalia Kaadan; Jude Foudeh; Tara Ghazi; Yumen Sijari; Maher Maaita (BMC, 2022)
Abstract Introduction In the Muslim world, the use and acceptance of long-term and permanent contraceptives were limited. Our aim was to investigate those limiting factors so we can help making these methods widely available and acceptable to the society. Methods and data analysis There were 1365 women from Facebook groups in the period 08/10/2020-8/11/2020. Participants were married women, living in Jordan. This was a cross-sectional study. Statistical Package for Social Sciences (SPSS), version 16, software was used for statistical analysis (Chicago, Illinois, USA). Results Among participants, 22.3% had never used any contraceptives. Non-hormonal IUCD was the most commonly used method. There was a statistically significant association between the use of hormonal IUCD and women's age, marriage duration, education and number of children (p < 0.0001). Tubal ligation was adopted by only 44 (3.22%) participants. 19.68% of participants declined tubal ligation merely due to religious issues. Women who completed only high school level of education underwent tubal ligation significantly more than those with university (Bachelor) and post-university (Master or PhD) degrees (p < 0.0001 and 0.026, respectively). Only 1.83% of women's partners underwent vasectomy, the majority of these vasectomies (72.0%) were done because of the need for lifelong contraception. Around 17% of women's partners had poor knowledge about vasectomy. Further, women's employment status (housewives or full-time employees) was found to be the only variable that affected acceptance of vasectomy (p = 0.0047). Conclusions Women endured a heavy burden of contraception. Cultural and religious taboos influenced tubal ligation. Vasectomy was still very rarely adopted by men due to the lack of knowledge about the procedure. Our results raised the need for further dissemination of contraception knowledge and counselling through the primary care and maternity centers, mosques and media in official, comprehensive and integrated programs. Future research is needed in the field of permanent contraceptive methods.